Pengembangan Media Pembelajaran Berbasis Quizizz pada Pembelajaran Pendidikan Agama Islam Materi Ibadah dalam Kurikulum Merdeka - Wardian Syah Nst; Zulhammi Zulhammi; Abdusima Nasution (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
Islamic Religious Education (IRE) learning at State Vocational High School 1 Barumun is still predominantly conducted through lecture-based methods and the use of textbooks. As a result, it tends to be less engaging and less effective in enhancing students’ understanding of worship-related materials, which are both conceptual and practical in nature. The lack of active student involvement and the limited use of educational technology present significant challenges in the digital era, especially considering that today’s students are digital natives who respond more positively to interactive and technology-based media. Therefore, there is a need for innovative, technology-integrated learning media that align with their characteristics and support the principles of the Merdeka Curriculum. This study employed a Research and Development (R&D) method using the ADDIE development model, involving IRE teachers and Phase E students (Grade 10). The instruments used included observation, interviews, questionnaires, tests, and expert validations in content, media, and language. The results showed that the developed media was highly valid (95.48%), highly practical (95.50% from teachers and 82.45% from students), and moderately effective, with an average N-Gain of 63.96. Thus, the Quizizz-based digital learning media is considered suitable for improving students’ understanding and active engagement in Islamic Religious Education.